Underwater image processing and analysis: A review - Jian, Muwei; Liu, Xiangyu; Luo, Hanjiang; Lu, Xiangwei; Yu, Hui; Dong, Junyu (Signal processing. Image communication, 2021)
With increasing attentions being drawn to the underwater observation and utilization of marine resources in recent years, underwater image processing and analysis have become an active research hotspot. Different from the general images, marine environment is usually faced with some complicated situations such as underwater turbulence and diffusion, severe absorption and scattering of water body, various noises, low contrast, uniform illumination, monotonous color, complex underwater-background. In response to these typical challenges, a large body of works in underwater image processing has been exploited in recent years. This survey introduces a review of existing relatively mature and representative underwater image processing models, which are classified into seven categories including enhancement, fog removal, noise reduction, segmentation, salient object detection, color constancy and restoration. We then objectively evaluate the current situations and future development trend of underwater image processing, and provide some insights into the prospective research directions to promote the development of underwater vision and beyond. •This survey introduces a review of existing representative underwater image processing models.•Future development trend of underwater image processing is introduced.•Some insights into the prospective research directions to promote the development of underwater vision are provided.